(untitled) (Bangladesh Journal of Medical Science, 2020)
Patients with systemic lupus erythematosus (SLE) going for surgery have put challenges to the treating surgeon, anaesthetist and physician as the patients can present with various medical complications perioperatively. It can be associated with polyarticular involvement especially avascular necrosis of the head of femur. The patients may present young with severe clinical findings and abnormal radiological features. The surgery in young SLE patients revolves on the longevity of the prosthesis used.We report a case of a 26-year-old lady with SLE going for right total hip replacement for her avascular necrosis of right hip. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.322-325